The relationship between depression, anxiety, chronic pain and pain pressure threshold of the masseter muscle in healthy young subjects. A pilot study - Kruk-Majtyka Weronika; Marciniak Tomasz (Biomedical Human Kinetics)
Study aim: The correlation between pain and emotional status in subjects with temporomandibular disorders (TMD) is established. Nevertheless, there is a lack of up-to-date findings based on objective assessment of pain using a digital algometer on the mastication muscles. The aim of this study was to investigate the relationship between the emotional status and the chronic pain pressure threshold (PPT).